Restorative justice: a new paradigm? - Monterosso, Stephen (The Icfai university press, 2009)
This article examines the merits of restorative justice within criminal justice system. The overpopulation of prisons remains a major global issue along with increasing rates of recidivism. In stark contrast to the punitive aims of traditional retributive justice systems that enforce a regime of punishment for offenders, the restorative justice approach promotes the repair of harm caused by an offence. The purpose of this article is to provide an overview of restorative justice in addition to examining potential barriers to its widespread application.